Hubungan Antara Motivasi Belajar dengan Resiliensi Akademik Pada Siswa Kelas X di SMK Negeri 6 Bandung - Dewi, Detisa Witri; Thahir, Muthahharah; Rachmaniar, Ananda (Ma'soem University, 2025)
The implementation of the Merdeka Curriculum requires students to be more independent, flexible, and active in the learning process. However, these changes are not easily adapted by all students. Some experience difficulties in adjusting, which affects their learning motivation and resilience in facing academic challenges. This study aims to describe learning motivation, academic resilience, and the relationship between the two among tenth-grade students at SMK Negeri 6 Bandung in the 2024–2025 academic year. This research uses a quantitative approach with a correlational method. A total of 272 students were selected proportionally as the sample. Data were collected using learning motivation and academic resilience scale questionnaires, then analyzed using descriptive and correlational techniques. The results showed that the majority of students had moderate levels of learning motivation (82%), while academic resilience was mostly in the high category (64%). Correlation analysis revealed a positive and significant relationship between learning motivation and academic resilience, with a correlation coefficient of 0.409 and a significance value of p < 0.001. These findings suggest that students with higher learning motivation tend to be more resilient in facing academic difficulties. Therefore, it is essential for schools to create adaptive learning environments that support the development of student motivation and resilience, especially in the face of educational challenges in the Merdeka Curriculum era.